Identical ratios: a red flag of ratio management - Ling, Qianhua; Roberts, Andrea Alston (Review of Accounting Studies, 2025)
Abstract This paper identifies a helpful red flag stakeholders can use to detect whether a nonprofit has managed its financial information. This red flag is reporting an identical program ratio—that is, the nonprofit organization reports the exact same ratio in multiple years—while reporting a large change in total spending. We find nonprofits are more likely to report identical program ratios when resource providers rely on ratios; pay is determined, at least in part, by performance; and the potential for regulatory interference is high. This paper also identifies the cost allocation techniques and the specific expenses nonprofits likely manage. We find most nonprofits alter the allocations of multiple expenses and find the specific expenses most likely manipulated are ones where managers have a high degree of discretion over how much to allocate to programs.